1994
DOI: 10.1172/jci117255
|View full text |Cite
|
Sign up to set email alerts
|

Dietary cholesterol and downregulation of cholesterol 7 alpha-hydroxylase and cholesterol absorption in African green monkeys.

Abstract: In this study, hepatic production of bile acid was considered together with intestinal cholesterol absorption as potential regulatory sites responsive to dietary cholesterol. Sequential liver biopsies were taken from 45 feral African green monkeys studied during three different diet periods. Low-fat Monkey Chow was fed during the baseline period, a cholesterol and fatenriched diet was then fed for 12 wk during period 2, and finally, after a washout period of 10 wk, three subgroups were fed low-, moderate-, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
42
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 40 publications
5
42
0
Order By: Relevance
“…Studies in mice show that many sterol regulatory element-binding proteins and liver X receptor-sensitive genes can be coordinately regulated at the transcriptional level in response to dietary cholesterol (7,8). In contrast to what has been described for rodents (7), liver X receptormediated regulation of the cholesterol 7␣-hydroxylase gene does not explain the down-regulation of this enzyme by dietary cholesterol in primates (9). Instead, cholesterol esterification enzymes are candidate sites for regulation.…”
mentioning
confidence: 88%
“…Studies in mice show that many sterol regulatory element-binding proteins and liver X receptor-sensitive genes can be coordinately regulated at the transcriptional level in response to dietary cholesterol (7,8). In contrast to what has been described for rodents (7), liver X receptormediated regulation of the cholesterol 7␣-hydroxylase gene does not explain the down-regulation of this enzyme by dietary cholesterol in primates (9). Instead, cholesterol esterification enzymes are candidate sites for regulation.…”
mentioning
confidence: 88%
“…Ϫ/Ϫ Mice Lack Induction of CYP7A1 Expression (12) and rabbits (35). The mechanism for this decrease is not immediately apparent, particularly in primates, although it has been suggested (36) that, in rabbits, there is induction of CYP7A1 with an increase in bile acid pool size that overrides the cholesterol effect and results in lowering of CYP7A1 expression through the FXR-mediated pathway.…”
Section: Cyp7a1mentioning
confidence: 99%
“…LXR induces transcription of a number of other genes involved in cholesterol disposition (11). In some species, cholesterol feeding leads to a decrease in CYP7A1 levels (12,13). In these cases, the increase in bile acid synthesis induced by cholesterol feeding may ultimately lead to suppression of CYP7A1 because of an expanded bile acid pool.…”
mentioning
confidence: 99%
“…It has been reported that rodents have a very hydrophilic bile acid pool, which is less potent in activation of FXR; thus, the LXRα could function as an important regulator of CYP7A1 in mice (Chiang et al, 2001). In contrast, CYP7A1 expression was down-regulated by a high-cholesterol diet in African green monkeys (Rudel et al, 1994) and in rabbits (Xu et al, 2003), since the inhibitory effect of FXR may override the stimulatory effect of LXRα. There are another Figure 7.…”
Section: Discussionmentioning
confidence: 99%